Impact of Mixing Methods and Concentrations on Corrosion Resistance of Smart Coating with Benzotriazole-Loaded Halloysite Nanotubes - Norshafiera Richard @ Iran; Puteri Sri Melor Megat Yusof; Nuur Fahanis Che Lah; Muhammad Yasir (Platform, a Journal of Engineering)
The oil and gas industry faces significant challenges due to pipeline corrosion, resulting in substantial economic losses and safety risks. This study investigates the effectiveness of smart coatings containing varying concentrations of benzotriazole-loaded halloysite nanotubes (BTA-HNT) and boiled linseed oil microcapsules (MCs) in mitigating corrosion and to investigate the impact of different mixing techniques on the performance of these coatings. Epoxy coatings incorporating BTA-HNT and MCs were applied to carbon steel substrates in concentrations of 10 wt%, 15 wt%, and 20 wt%. Two mixing methods, magnetic stirring and sonication, were assessed for their ability to disperse the microcapsules effectively. Characterisation techniques, including FTIR, EDX, and particle size analysis, confirmed successful encapsulation and uniform distribution of the microcapsules. Electrochemical Impedance Spectroscopy (EIS) and scratch tests revealed that coatings with 15 wt% BTA-HNT and MCs, prepared using sonication, provided superior long-term corrosion protection and self-healing capabilities. Additionally, adhesion tests demonstrated that sonicated samples maintained stronger bonding. These findings highlight the crucial role of microcapsule concentration and mixing techniques in optimising the performance of self-healing epoxy coatings, offering promising solutions for enhanced durability and protection in pipeline infrastructure.